2003
DOI: 10.1165/rcmb.2002-0314oc
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic Effects of Parathyroid Hormone-Related Protein in Type II Pneumocytes

Abstract: Parathyroid hormone-related protein (PTHrP) promotes or suppresses apoptosis in various settings depending on cell type and context. PTHrP 1-34 and PTHrP 67-86 are type II cell growth factors with effects on pneumocyte growth and surfactant secretion. This study investigated the effects of 24 h pretreatment with these two peptides on rat type II cell apoptosis after 0.3 J/cm2 ultraviolet-B irradiation. Adherent cells decreased in number by 15 +/- 5% and nonadherent cells increased > 5-fold 24 h after ultraviol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In contrast, PTHrP-(1-34) is proapoptotic in HEK-293 embryonic human kidney cells by acting through a G q -mediated phospholipase C-Ca 2ϩ signaling pathway (33). In alveolar epithelial cells, protective effects against apoptosis are apparently mediated through a PKC-dependent pathway (13). Further work is necessary to establish the signaling mechanisms for PTHrP-(1-34) and PTHrP-(140-173) in lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, PTHrP-(1-34) is proapoptotic in HEK-293 embryonic human kidney cells by acting through a G q -mediated phospholipase C-Ca 2ϩ signaling pathway (33). In alveolar epithelial cells, protective effects against apoptosis are apparently mediated through a PKC-dependent pathway (13). Further work is necessary to establish the signaling mechanisms for PTHrP-(1-34) and PTHrP-(140-173) in lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear condensation was quantified as described previously (13). Adherent cells in Slide-Tek wells were washed with PBS and fixed with 100% methanol.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…cAMP and inositol phosphates were measured with protocols described previously (12). Cells were washed twice with PBS and incubated for 30 min in serum-free medium before application of agonists.…”
Section: Second Messenger Assaysmentioning
confidence: 99%
“…For example, PTHrP 67-86 has antimitogenic effects on selected breast carcinoma cell lines (18,19). We recently demonstrated that PTHrP 1-34 and PTHrP 67-86 both sensitize type II cells to apoptosis after exposure to ultraviolet radiation (13). Both peptides cause a rapid increase in pneumocyte inositol phosphate levels.…”
Section: Discussionmentioning
confidence: 99%